SEROLOGIC SURVEY FOR LEPTOSPIRA SPP. IN CAPTIVE NEOTROPICAL FELIDS IN FOZ do IGUACU, PARANA, BRAZIL - Ullmann, Leila Sabrina [UNESP]; Hoffmann, Juliano L. [UNESP]; de Moraes, Wanderlei; Cubas, Zalmir S.; dos Santos, Leonilda Correia; da Silva, Rodrigo Costa [UNESP]; Moreira, Nei; Sa Guimaraes, Ana Marcia; Camossi, Lucilene Granuzzio [UNESP]; Langoni, Hélio [UNESP]; Biondo, Alexander W. (Amer Assoc Zoo Veterinarians, 2012)
Leptospirosis is a bacterial zoonosis of worldwide distribution and is endemic in tropical countries, where rodents and other wild mammals are abundant and may act as reservoirs. Leptospirosis has become a concern in captive wild animals, due mostly to their exposure to contaminated urine or environment. Although domestic cats (Felis catus) have been reported refractory to leptospirosis, serology and disease in captive wild felids is still unclear. In this study 57 adult, clinically healthy felids, including 1 Geoffroy's cat (Leopardus geoffroyi), 3 jaguarundis (Puma yagouaroundi), 17 margays (Leopardus wiedii), 22 little spotted cats (Leopardus tigrinus), and 14 ocelots (Leopardus pardalis) kept in captivity at the Sanctuary at the Itaipu Binacional hydroelectric power plant (Bela Vista Biological Sanctuary), Foz do Iguacu City, Parana State, Brazil, were serologically surveyed for the presence of antibodies against 28 serovars of Leptospira spp. by microagglutination test (MAT). Two animals (3.5%) were seropositive: one male ocelot to the serovar Cynopteri (titer 100) and one female margay to Autumnalis (100) and Butembo (200). The captive-born, 5-yr-old ocelot had been solitary housed in an individual cage. The approximately 21-yr-old wild-caught margay was also kept individually. None of the tested animals showed signs of leptospirosis. During a study conducted 4 yr previously in the same facility, this particular margay also tested positive for the same two serovars, among others. The present study indicates that the felids tested for Leptospira spp. by MAT were exposed to serovars, but did not demonstrate clinical signs of disease. Comparison with a previous study suggests that serovar titers may vary over time and that leptospirosis dynamics remains unclear in wild felids.
Keywords: Captive wild cats; leptospirosis; microagglutination test; serology